2020
DOI: 10.18632/aging.102943
|View full text |Cite
|
Sign up to set email alerts
|

Genetic networks in Parkinson’s and Alzheimer’s disease

Abstract: Parkinson's disease (PD) and Alzheimer's disease (AD) are the most common neurodegenerative diseases and there is increasing evidence that they share common physiological and pathological links. Here we have conducted the largest network analysis of PD and AD based on their gene expressions in blood to date. We identified modules that were not preserved between disease and healthy control (HC) networks, and important hub genes and transcription factors (TFs) in these modules. We highlighted that the PD module … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 76 publications
0
25
0
Order By: Relevance
“…In the current study, we explored AD-related biological processes by analysing the coexpression gene modules of different brain regions in different disease stages. The coexpression network features and key genes of AD peripheral blood or brain have been reported in several previous studies (Seyfried et al, 2017;Liang et al, 2018;Sweeney et al, 2018;Zhang et al, 2018;Hu et al, 2020;Kelly et al, 2020;Soleimani Zakeri et al, 2020). Among these studies, Wang et al performed a pan-cortical brain region genomic analysis, obtained and ranked 44,692 gene probesets, 1,558 coexpressed gene modules and 19 brain regions based upon their association with AD; through these analyses temporal lobe gyri were identified as sites associated with the greatest and earliest gene expression abnormalities, abnormal expression was specific to cell type of oligodendrocytes, astrocytes, and neurons, and neurobiological pathways (included actin cytoskeleton, axon guidance, and nervous system development) were enriched by abnormally expressed genes and modules (Wang et al, 2016); however, the changes in coexpression modules in sub-brain regions during AD development have not been fully studied.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In the current study, we explored AD-related biological processes by analysing the coexpression gene modules of different brain regions in different disease stages. The coexpression network features and key genes of AD peripheral blood or brain have been reported in several previous studies (Seyfried et al, 2017;Liang et al, 2018;Sweeney et al, 2018;Zhang et al, 2018;Hu et al, 2020;Kelly et al, 2020;Soleimani Zakeri et al, 2020). Among these studies, Wang et al performed a pan-cortical brain region genomic analysis, obtained and ranked 44,692 gene probesets, 1,558 coexpressed gene modules and 19 brain regions based upon their association with AD; through these analyses temporal lobe gyri were identified as sites associated with the greatest and earliest gene expression abnormalities, abnormal expression was specific to cell type of oligodendrocytes, astrocytes, and neurons, and neurobiological pathways (included actin cytoskeleton, axon guidance, and nervous system development) were enriched by abnormally expressed genes and modules (Wang et al, 2016); however, the changes in coexpression modules in sub-brain regions during AD development have not been fully studied.…”
Section: Discussionmentioning
confidence: 80%
“…In addition to finding differentially expressed genes (DEGs) that are significantly changed in AD patients, expression profiling can also provide more evidence about the systematic molecular processes underlying the etio-pathogenesis of AD. Based upon the associations between coexpressed gene modules and AD traits, several previous studies identified AD-related gene modules, which suggests that the biological processes that these genes contribute to may be affected in AD (Wang et al, 2016;Tang and Liu, 2019;Hu et al, 2020;Kelly et al, 2020). By using spatial-temporal expression pattern analysis, transcriptome data can also provide evidence about specific brain regions and cell types that are possibly related to AD (Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…KEGG analysis revealed that DEGs in the brain were significantly enriched in neuroactive ligand-receptor interaction, consistent with a previous study. They reported that the regulation of neuroactive ligand-receptor interaction associated with AD was not preserved in healthy and MCI networks [ 64 ]. Another multinational study confirmed that genes regarding neuroactive ligand-receptor interaction were closely related to memory-modulation [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is used to collate the counsel due to gene expression (Zhang et al, 2016). In (Kelly et al, 2020) the authors carried out a huge up to date probe of AD network in blood depending on its gene expressions. They located among the networks of disease and healthy control, the un-conserved modules and pertinent genes as hub with transcription factors.…”
Section: Genetic Network and Admentioning
confidence: 99%
“…Here the vital TRPC5 and BRAP lots are conceived as main targets for treatments of therapeutic type. Their investigation showed that AD possess in common genetics that are impaired and located pathways that are interesting (Kelly et al, 2020).…”
Section: Genetic Network and Admentioning
confidence: 99%